Human Milk Oligosaccharides Modulate Fecal Microbiota and Are Safe for Use in Children With Overweight: A Randomized Controlled Trial. Issue 3 (16th September 2021) - Fonvig, Cilius Esmann; Amundsen, Ingvild Dybdrodt; Vigsnæs, Louise Kristine; Sørensen, Nikolaj; Frithioff-Bøjsøe, Christine; Christiansen, Michael; Hedley, Paula Louise; Holm, Louise Aas; McConnell, Bruce; Holm, Jens-Christian
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: Human milk oligosaccharides (HMOs) impact the intestinal microbiota by increasing beneficial bacteria in infants and adults, and are safe and well tolerated in these age groups. Effects on intestinal microbiota, safety, and digestive tolerance in children have not been, however, assessed. The aims of this trial were to evaluate if HMOs are able to specifically modulate the intestinal microbiota in children, and to assess safety and digestive tolerance. Methods: In this randomized, double-blinded, placebo-controlled trial, 75 children with overweight (including obesity) ages 6 to 12 years were randomized to receive 2′-fucosyllactose (2′FL), a mix of 2′FL and lacto-N-neotetraose (Mix), or a glucose placebo orally administrated once per day for 8 weeks. Results: The relative abundance of bifidobacteria increased significantly after 4 ( P  < 0.001) and 8 ( P  = 0.025) weeks of intervention in the 2′FL-group and after 4 weeks ( P  = 0.033) in the Mix-group, whereas no change was observed in the placebo group. Compared with placebo, the 2′FL-group had a significant increase in bifidobacteria abundance after 4 weeks ( P  < 0.001) and 8 weeks ( P  = 0.010) and the Mix-group showed a tendency to increased bifidobacteria abundance after 4 ( P  = 0.071) and 8 weeks ( P  = 0.071). Bifidobacterium adolescentis drove the bifidogenic effect in the 2 groups. Biochemical markers indicated no safety concerns, and the products did not induce digestive tolerance issues as assessed by Gastrointestinal Symptoms Rating Scale and Bristol Stool Form Scale. Conclusions: Both 2′FL and the Mix beneficially modulate intestinal microbiota by increasing bifidobacteria. Furthermore, supplementation with either 2′FL alone or a Mix is safe and well tolerated in children.